Invariant solutions of a system of Euler equations that satisfy the Rankine—Hugoniot conditions - Yuryk, I.I. (Доповіді НАН України, 2018)
We consider equations of hydrodynamics with certain additional constraints. Group-theoretical methods are applied
to find invariant solutions of a system of Euler equations that satisfy the Rankine–Hugoniot conditions. Розглядаються рівняння гідродинаміки з певними додатковими обмеженнями. Для пошуку інваріантних
розв'язків системи рівнянь Ейлера, що задовольняють умови Ренкіна—Гюгоніо, застосовуються теоретико-групові методи. Рассматриваются уравнения гидродинамики с некоторыми дополнительными ограничениями. Для нахождения инвариантных решений системы уравнений Эйлера, удовлетворяющих условиям Ренкина—Гюгонио, применяются теоретико-групповые методы.